2015
DOI: 10.1002/pip.2603
|View full text |Cite
|
Sign up to set email alerts
|

CuOx/a‐Si:H heterojunction thin‐film solar cell with an n‐type µc‐Si:H depletion‐assisting layer

Abstract: We showed that thin n-type CuO x films can be deposited by radio-frequency magnetron reactive sputtering and demonstrated the fabrication of n-CuO x /intrinsic hydrogenated amorphous silicon (i-a-Si:H) heterojunction solar cells (HSCs) for the first time. A highly n-doped hydrogenated microcrystalline Si (n-μc-Si:H) layer was introduced as a depletionassisting layer to further improve the performance of n-CuO x /i-a-Si:H HSCs. An analysis of the external quantum efficiency and energy-band diagram showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…This suggestion is supported by previous literature that points to the creation of n-type Cu x O given a relatively high (>50% PO 2 ) [15] or low introduction of oxygen (e.g. Cu-rich) during deposition [15,16]. The high initial resistance of this memristor (on the order of 10 9 ohms) versus the resistance of the previous memristor (on the order of 10 5 ohms) shows evidence of relatively high oxygen concentration in spite of both devices being the same thicknesses.…”
Section: Mechanism Of Gas Detectionsupporting
confidence: 86%
“…This suggestion is supported by previous literature that points to the creation of n-type Cu x O given a relatively high (>50% PO 2 ) [15] or low introduction of oxygen (e.g. Cu-rich) during deposition [15,16]. The high initial resistance of this memristor (on the order of 10 9 ohms) versus the resistance of the previous memristor (on the order of 10 5 ohms) shows evidence of relatively high oxygen concentration in spite of both devices being the same thicknesses.…”
Section: Mechanism Of Gas Detectionsupporting
confidence: 86%
“…A deposition process called successive ion layer adsorption and reaction (SILAR) that can deposit Cu 2 O and CuO at mild solution process conditions without ion bombardment is especially promising [ 65 ]. The recent observation of n-type behavior in CuO x suggests that CuO/CuO x junctions should be fabricated by sputtering and investigated for homojunction behavior [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the CuO devices discussed thus far, the sputtered CuO layer is always p-type. Recently, however, Lee et al has observed n-type behavior in nanoscale non-stoichiometric CuO x deposited by reactive magnetron sputtering [ 46 ]. The n-type conductivity which was confirmed by Hall effect measurements results from the fact that in the initial stage of deposition, the CuO x is Cu rich and this causes electrons to be majority carriers.…”
Section: Cuo Thin Film Heterojunction Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively smaller band gap of CuO makes it a potentially superior material for photo-detection and optical switching applications in the visible or near-infrared region in comparison to other large band-gap metal oxides [12,13]. Reports are available on the development of CuO based renewable energy technologies by exploiting its efficient solar absorbance and low thermal emittance properties [9,[13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%